ANALISIS TERHADAP TINDAK PIDANA KORUPSI PENYALAHGUNAAN WEWENANG DALAM JABATAN PEMERINTAHAN - wati, endra (Morality: Jurnal Ilmu Hukum; Vol 3 No 2 (2017): Jurnal Ilmu Hukum Morality, 2018)
Abstract : Corruption is one of white collar crime or white collar crime where corruption case is done by state apparatus whether civil servant or state official indicates that not only poverty is the cause of the crime, but the prosperity factor because of corruption concerning moral aspect, rotten nature and circumstances, positions in government agencies or apparatuses, abuse of power in office. The problems that occur are what are the factors causing the criminal act of corruption of abuse of authority in the office and how the effort to overcome the corruption crime of abuse of authority in government office in Palangkaraya. The problem approach used to answer the above problems is the juridical normative and juridical empirical approach. Based on the results of research and discussion, factors causing criminal corruption abuse of authority in government office consists of two factors, namely internal factors and external factors. Internal factors (derived from within the human), namely the personality factor (greedy nature) while the external factors of opportunity factors, economic factors (consumptive lifestyle), religious factors and occupational factors. Efforts to tackle criminal acts of corruption in office abuse are preventive measures by increasing supervision of state apparatus. Efforts to overcome by way of giving criminal sanction according to Law no. 31 of 1999 as amended by Law no. 20 Year 2001 on the Eradication of Corruption. Keywords : Corruption, government position